2007
DOI: 10.1038/sj.eye.6702856
|View full text |Cite
|
Sign up to set email alerts
|

Variables affecting refractive outcome following LASIK for myopia

Abstract: Aim To investigate factors affecting refractive outcome following LASIK for myopia. Method Six hundred and seventy-four consecutive uncomplicated myopic LASIK surgeries, performed by a single surgeon, either using the Technolas 217 planoscan (n ¼ 372) or the NIDEK EC 5000 (n ¼ 302), were evaluated. Stratified random sampling was used to match the groups for refractive error, patient age, and gender. The final analysis included 302 patients from each treatment group. Conditions were identical for both surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some reports have found that age is a factor, with younger patients having better outcomes, but other studies have not found an association. 9,19,20 In addition, studies of the possible benefi t of femtosecond-created LASIK fl aps have shown both similar and improved outcomes compared to mechanical keratome-created fl aps. 4,[21][22][23][24] Given these mixed results, it is not known whether patients who did not attend the 1-month examination would have collectively done better, worse, or the same as the cohort who attended the 1-month examination.…”
Section: Snellen Linesmentioning
confidence: 99%
“…Some reports have found that age is a factor, with younger patients having better outcomes, but other studies have not found an association. 9,19,20 In addition, studies of the possible benefi t of femtosecond-created LASIK fl aps have shown both similar and improved outcomes compared to mechanical keratome-created fl aps. 4,[21][22][23][24] Given these mixed results, it is not known whether patients who did not attend the 1-month examination would have collectively done better, worse, or the same as the cohort who attended the 1-month examination.…”
Section: Snellen Linesmentioning
confidence: 99%
“…Unfortunately, due to the limited information supplied to eye banks, most of the clinical details of the patient were unknown, but the results clearly demonstrate the lack of long-term wound healing at the flap margins and across the flap bed. It should however be noted the patient was 50 years old at the time of surgery and there is a significant trend for increased refractive failure with increasing patient age suggesting that stromal changes with age may have influenced post-operative healing [11], [12].…”
Section: Discussionmentioning
confidence: 99%
“…Visual outcome is similarly enhanced by matching the patient characteristics with the appropriate surgery. Several variables may influence this decision for the refractive surgeon, including magnitude of refractive error, corneal and ocular health and patient age …”
Section: Patient Selectionmentioning
confidence: 99%
“…Several variables may influence this decision for the refractive surgeon, including magnitude of refractive error, corneal and ocular health and patient age. 16 Prior to proceeding with surgery, a comprehensive visual and ocular assessment is vital to assess the suitability of the procedure. Patients who routinely wear contact lenses must have them out for a minimum period: three days for soft contact lenses and three weeks for gas-permeable or hard contact lenses.…”
Section: Patient Selectionmentioning
confidence: 99%